BIOPRODUKSI FLOROGLUSINOL OLEH JAMUR ENDOFIT COELOMYCETES AFAS-F3 YANG DIISOLASI DARI TUMBUHAN Archangelesia flava L. MERR. - Yuliasri Jamal; Praptiwi; Ahmad Fathoni; Andria Agusta (The East Java Biological Society, 2011)
Isolation and identification of secondary metabolites of endophytic fungus associated with the plant of Archangelisia flava Merr. and antibacterial activity test were done in this study. Extraction of biomass of endophytic fungus culture and its secondary metabolites isolation were done in ethyl acetate and methanol solvent then followed by thin layer and colomn chromatography. The fractions from colomn chromatography were tested for antibacterial activity against Escherichia coli by paper disc method. The result showed that the extract composed of 9 fractions. Fraction 4th and 8th had growth inhibition zone, 8 mm and 10 mm respectively, against E.coli at the concentration of 100 mg/ml. Isolation and purifi cation process through several chromatography techniques yielded one major metabolites wich was identifi ed as phloroglucinol by co-chromatography technique on a GC-MS machine. Phloroglucinol can produce 10 mm clear zone on a disc antibacterial assay against E. coli.